RANCANG BANGUN SISTEM MONITORING SUHU DAN KELEMBABAN BERBASIS ARDUINO UNO UNTUK SMART HOME - Aziz Asmauna; Muhammad Naim; M Yasir Pohan (LPPM Universitas Cipta Mandiri, 2026)
This research aims to design and build a room temperature and humidity monitoring system based onthe Arduino Uno microcontroller that can be applied to smart homes. This system uses a DHT11sensor to read ambient temperature and humidity, then displays the data on a 16x2 LCD and sendsthe data to the user's smartphone via the HC-05 Bluetooth module. Test results show that the systemcan read temperature with an accuracy of ±1°C and humidity of ±5% RH. The system successfullyoperated stably for 72 hours of continuous testing with an average power consumption of 0.5 watts.This system implementation can help homeowners monitor environmental conditions in real time forcomfort and energy efficiency.